Human rights and international relations - R J Vincent (Cambridge Univ. Press, 1987)
The book is about the impact of human rights on the relations among states. It seeks to bring together in one place an account of the theory of human rights; a discussion of the part they play in contemporary international politics; and a view of what ought to be done about them - especially by the western powers